Improved bounds on number fields of small degree - Theresa C. Anderson; Ayla Gafni; Kevin Hughes; Robert J. Lemke Oliver; David Lowry-Duda; Frank Thorne; Jiuya Wang; Ruixiang Zhang (Discrete Analysis)
Improved bounds on number fields of small degree, Discrete Analysis 2024:19, 24 pp.